ANALISIS PENINGKATAN KOMPETENSI KOMUNIKASI MAHASISWA MELALUI PROGRAM MAGANG KAMPUS BERDAMPAK PADA DIVISI REDAKSI DIGITAL SUMEKS.CO - Muhamad Tino Nopriansyah; Isnawijayani Isnawijayani (JOURNAL SAINS STUDENT RESEARCH, 2026)
The rapid development of the cyber media industry demands communication students not only to master classroom theories but also to possess adaptive practical competencies tailored to the digital ecosystem. The Impactful Campus Internship Program serves as a crucial bridge aligning industry requirements with students' academic capacities. This study aims to analyze the enhancement of students' communication competence through the implementation of the Impactful Campus Internship at the Digital Editorial Division of SUMEKS.CO, specifically across interpersonal, professional, and multimedia-based mass communication dimensions. ​This study employed a descriptive qualitative approach. Data collection was carried out through participatory observation during the 16-week internship period (February–June 2026), semi-structured interviews with field supervisors, and documentation of the entire work portfolio produced within the digital editorial division. Data validity was ensured through source and method triangulation techniques. The conceptual framework used to examine this phenomenon includes David A. Kolb’s Experiential Learning Theory, Contemporary Journalism Theory, and Digital Media Theory. ​The results of the study indicated that internship activities in the Digital Editorial Division of SUMEKS.CO successfully facilitated a significant increase in students' communication competence through direct involvement in multimedia content production. Throughout the internship period, the student successfully produced a tangible portfolio consisting of 4 creative video contents for Instagram Reels and wrote as well as published dozens of digital journalistic articles across various main rubrics, including Game, Local News, Automotive, Lifestyle, Health, and Business. Through the experiential learning cycle (concrete experience, reflective observation, abstract conceptualization, and active experimentation), the student not only mastered cyber newsroom workflows and journalistic regulations but also improved interpersonal skills, teamwork, copywriting techniques, adaptation to video editing technologies, and basic Search Engine Optimization (SEO) understanding. This study concludes that the Impactful Campus Internship program at the Digital Editorial Division of SUMEKS.CO is highly effective in transforming students' theoretical knowledge into ready-to-use practical-professional competencies in the modern media industry.